Modelling and validation of the antifungal activity of DL-3-phenyllactic acid and acetic acid on bread spoilage moulds. (June 2020) - Debonne, Els; Vermeulen, An; Bouboutiefski, Naomi; Ruyssen, Tony; Van Bockstaele, Filip; Eeckhout, Mia; Devlieghere, Frank
Abstract: Most interesting antifungal compounds from sourdough fermentation are acetic acid (AA) and DL-3-phenyllactic acid (PLA). Although the role of pH on the activity of organic acids has been established long time ago, no information is available on the importance of undissociated acid (HA) expressed on the aqueous phase of bread (CHA, mmole/L). Mostly, concentrations (mmole/kg dough or bread, CTOT ) and pH are given side by side. The aim of this study was to show the importance of CHA for adequate comparison of in-vitro growth data with bread shelf-life. Growth of Penicillium paneum and Aspergillus niger was recorded using a micro-dilution assay with optical density measurements. Parameters such as aw (0.94–0.98), pH (4.6–6.0), temperature (10–30 °C), time (0–8 days) and CTOT (0–300 mM) were varied. Growth/no-growth models were developed and shelf-life tests of par-baked breads of 45 days at 20 °C were conducted. The modelled inhibitory concentrations of undissociated acid were comparable with the shelf-life test of bread: (PLA) 50 versus 39–84 mmol/L; (AA) 110 versus 110–169 mmol/L. This study showed the applicability of G/NG models for bread shelf-life prediction and highlighted the importance of CHA. Moreover, it was found that naturally present PLA in sourdough bread is insufficient to increase bread shelf-life. Highlights: Growth/no-growth models (G/NG) were produced based on data of micro-dilution assays. G/NG models of acetic acid and phenyllactic acid were developed for P. paneum and A. niger. Acid concentrations must be expressed in mmole undissociated acid per L aqueous phase (CHA ). A CHA of 110–169 mM of acetic acid in par-baked bread prevents mould growth during 45 days. Phenyllactic acid in sourdough bread does not perform antifungal activity.